Dual-effects of caffeinated hyalurosomes as a nano-cosmeceutical gel counteracting UV-induced skin ageing - Manal A Elsheikh; Passent M.E. Gaafar; Mohamed A. Khattab; Mohamed Kamal A. Helwah; Mohamed H. Noureldin; Haidy Abbas (Elsevier, 2023)
Caffeine (CAF) is a challenging natural bioactive compound with proven antiaging efficacy. However, being hydrophilic hampers its permeation through the skin. Our aim is to develop a novel CAF-loaded nano-cosmeceutical tool counteracting skin photoaging via improving CAF skin permeation using a bioactive nanocarrier. Caffeinated hyalurosomes are novel biocompatible antiaging nanoplatforms designed by immobilization of phospholipid vesicles with a hyaluronan polymer. Physicochemical properties of the selected hyalurosomes formulation showed nano-sized vesicles (210.10 ± 1.87 nm), with high zeta potential (−31.30 ± 1.19 mv), and high encapsulation efficiency (84.60 ± 1.05%). In vitro release results showed outstanding sustained release profile from caffeinated hyalurosomes compared to the CAF-loaded in conventional gel over 24 h. The in-vivo study revealed a photoprotective effect of caffeinated hyalurosomes, reflected from the intact and wrinkling-free skin. Results of biochemical analyses of oxidative stress, pro-inflammatory mediators, and anti-wrinkling markers further confirmed the efficacy of the prepared hyalurosomes compared to the CAF conventional gel. Finally, histopathological examination demonstrated normal histological structures of epidermal layers with minimal inflammatory cell infiltrates in the caffeinated hyalurosomes group compared to the positive control group. Conclusively, caffeinated hyalurosomes successfully achieved enhanced CAF loading and penetration into the skin besides the hydration effect of hyaluronan. Consequently, the developed delivery system presents a promising skin protection nano-platforms via the double effects of both hyaluronan and CAF, hence it guards against skin photodamage.